Analisis Semiotika Gejala Post Traumatic Stress Disorder dalam Serial Stranger Things Season 4 - Angelyn, Felycia; Winduwati, Septia (Koneksi, 2023)
The state of mass communication currently functions as a transmission of values and social representation in society, one of which is the Stranger Things Season 4 Series. This series is a work of fiction that raises the issue of mental health. The focus of this research is to show how the symptoms of Post-Traumatic Stress Disorder (PTSD) are manifested in the characters of Max Mayfield and Chrissy Cunningham through the scenes observed and chosen by the researcher. The theoretical concepts used in this study are mass communication, communication psychology, and semiotics. This study uses a qualitative method research approach with Charles Sanders Pierce's semiotic analysis technique. The researcher collects and completes the data analysis by interviewing expert sources, studying documentation, and studying the literature. The result of this study is the Stranger Things Season 4 series as a mass communication work, wants to show a representation of social reality related to PTSD symptoms. PTSD symptoms are represented mostly through non-verbal signs such as (a) eyes that are not focused but when they feel cornered their gaze changes to a sharp one (b) tone of voice that seems hesitant in answering but rises when they are offended (c) facial expressions that significantly change according to the context of the conversation (d) repetitive hand and foot movements (e) actions shown such as when taking medicine, vomiting, and protecting oneself by sitting while covering one's ears in the corner of the toilet cubicle when under hallucination. Furthermore, The Stranger Things Season 4 series also conveys a message to the audience that a child can experience trauma as a result of parental verbal abuse. Kemajuan komunikasi massa saat ini berfungsi sebagai transmisi nilai dan representasi sosial di masyarakat salah satunya Serial Stranger Things Season 4. Serial ini merupakan karya fiksi yang mengangkat isu kesehatan mental. Fokus dari penelitian ini adalah untuk menunjukkan bagaimana gejala-gejala Post Traumatic Stress Disorder (PTSD) diangkat pada karakter Max Mayfield dan Chrissy Cunningham melalui adegan-adegan yang telah dipilih peneliti. Konsep teori yang digunakan dalam penelitian ini adalah komunikasi massa, psikologi komunikasi, dan semiotika. Penelitian ini menggunakan pendekatan penelitian metode kualitatif dengan teknik analisis semiotika Charles Sanders Pierce. Peneliti mengumpulkan dan melengkapi data analisis dengan cara wawancara narasumber ahli, studi dokumentasi, dan studi pustaka. Hasil dari penelitian ini adalah serial Stranger Things Season 4 sebagai karya komunikasi massa ingin menunjukkan representasi realita sosial terkait dengan gejala PTSD. Gejala PTSD direpresentasikan paling banyak melalui tanda non verbal seperti (a) tatapan mata yang tidak fokus namun saat merasa tersudutkan tatapannya berubah menjadi tajam (b) nada bicara yang terkesan ragu dalam menjawab namun meninggi ketika sedang tersinggung (c) raut wajah yang secara signifikan berubah sesuai konteks percakapan (d) gerakan tangan dan kaki yang dilakukan secara berulang (e) tindakan yang diperlihatkan seperti saat meminum obat, memuntahkan sesuatu, dan melindungi diri dengan duduk sambil menutup telinga di sudut bilik toilet saat berhalusinasi. Serial Stranger Things Season 4 juga menyampaikan pesan kepada audiens bahwa seorang anak dapat mengalami trauma akibat kekerasan verbal yang dilontarkan oleh orang tua.